Hypermelanic sebaceous nevus reminiscent of melanoma. - Cirfera, V. (European Journal of Pediatric Dermatology, 2018)
The Author reported two cases of sebaceous nevus characterized by the hyperproduction of melanin, in the first case histologically proven by the presence of a melanin excess in the basal layer of the epidermis, in the second case dermatoscopically hypothesized due to the presence of brownish dots and globules. Being absent at birtht the overproduction of melanin occurred in the peripuberal period suggesting a role of hormonal factors. In the first case, the physical examination was reminiscent of melanoma; however, the careful evaluation of the history, physical examination and dermatoscopic findings led to exclude this hypothesis.